If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(2y + 6) = 16 Reorder the terms: -4(6 + 2y) = 16 (6 * -4 + 2y * -4) = 16 (-24 + -8y) = 16 Solving -24 + -8y = 16 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + -8y = 16 + 24 Combine like terms: -24 + 24 = 0 0 + -8y = 16 + 24 -8y = 16 + 24 Combine like terms: 16 + 24 = 40 -8y = 40 Divide each side by '-8'. y = -5 Simplifying y = -5
| -1.4(5-x)+2.5(2+x)=-3.6+x | | -2u+14+3=8u+27 | | 3a+3=3 | | 7y+5+3y+4+14y-15=180 | | 3x-86=49-6x | | 7n-8=-16+3n | | 5x(x+7)=20 | | -3(x-2)+4(2x+5)=10x-(5x-23) | | x+7+z=-11 | | -20-7x=16+9x | | 90x=585 | | 36-14x=8 | | 5x=4+-4+5x | | 20(5)=20q+5 | | 8n-2=19+5n | | 6t-12-(3t-3)=-19 | | 2(x-1)+3(x+2)=5x+4 | | 2(2x)+47=2(2x)+47 | | -40+3x=10+2x | | 6x-12=5x+17 | | 6(y-24)-6y=0 | | -40+3x=2x | | 4*x-17=23 | | 4x+x^2=179 | | 6-x=10-2x | | 4y+4x=12 | | 2x+x+2(2)+75=180 | | 20=16(16)+b*b | | 11x-66=7x+34 | | 5gf^2+g^2f+15gf= | | 9(2p-1)= | | 9t=-2t^3-9t^2 |